Monitoring geological storage of CO2: a new approach - Manzar Fawad (Nature Portfolio, 2021)
Abstract Geological CO2 storage can be employed to reduce greenhouse gas emissions to the atmosphere. Depleted oil and gas reservoirs, deep saline aquifers, and coal beds are considered to be viable subsurface CO2 storage options. Remote monitoring is essential for observing CO2 plume migration and potential leak detection during and after injection. Leak detection is probably the main risk, though overall monitoring for the plume boundaries and verification of stored volumes are also necessary. There are many effective remote CO2 monitoring techniques with various benefits and limitations. We suggest a new approach using a combination of repeated seismic and electromagnetic surveys to delineate CO2 plume and estimate the gas saturation in a saline reservoir during the lifetime of a storage site. This study deals with the CO2 plume delineation and saturation estimation using a combination of seismic and electromagnetic or controlled-source electromagnetic (EM/CSEM) synthetic data. We assumed two scenarios over a period of 40 years; Case 1 was modeled assuming both seismic and EM repeated surveys were acquired, whereas, in Case 2, repeated EM surveys were taken with only before injection (baseline) 3D seismic data available. Our results show that monitoring the CO2 plume in terms of extent and saturation is possible both by (i) using a repeated seismic and electromagnetic, and (ii) using a baseline seismic in combination with repeated electromagnetic data. Due to the nature of the seismic and EM techniques, spatial coverage from the reservoir's base to the surface makes it possible to detect the CO2 plume’s lateral and vertical migration. However, the CSEM low resolution and depth uncertainties are some limitations that need consideration. These results also have implications for monitoring oil production—especially with water flooding, hydrocarbon exploration, and freshwater aquifer identification.